Muscle cell identity requires Pax7-mediated lineage-specific DNA demethylation. Issue 1 (December 2016) - Carrió, Elvira; Magli, Alessandro; Muñoz, Mar; Peinado, Miguel; Perlingeiro, Rita; Suelves, Mònica
Abstract Background Skeletal muscle stem cells enable the formation, growth, maintenance, and regeneration of skeletal muscle throughout life. The regeneration process is compromised in several pathological conditions, and muscle progenitors derived from pluripotent stem cells have been suggested as a potential therapeutic source for tissue replacement. DNA methylation is an important epigenetic mechanism in the setting and maintenance of cellular identity, but its role in stem cell determination towards the myogenic lineage is unknown. Here we addressed the DNA methylation dynamics of the major genes orchestrating the myogenic determination and differentiation programs in embryonic stem (ES) cells, theirPax7 -induced myogenic derivatives, and muscle stem cells in proliferating and differentiating conditions. Results Our data showed a common muscle-specific DNA demethylation signature required to acquire and maintain the muscle-cell identity. This specific-DNA demethylation is Pax7-mediated, and it is a prime event in muscle stem cells gene activation. Notably, downregulation of the demethylation-related enzyme Apobec2 in ES-derived myogenic precursors reduced myogenin-associated DNA demethylation and dramatically impaired the expression of differentiation markers and, ultimately, muscle differentiation. Conclusions Our results underscore DNA demethylation as a key mechanism driving myogenesis and identify specific Pax7-mediated DNA demethylation signatures to acquire and maintain the muscle-cell identity. Additionally, we provide a panel of epigenetic markers for the efficient and safe generation of ES- and induced pluripotent stem cell (iPS)-derived myogenic progenitors for therapeutic applications.